RHINOLARYNGOLOGICAL AND SYSTEMIC CAUSES OF HALITOSIS: A MINI-REVIEW - Rasouli, Abdul Azeem; Momand, Sadaqat; Taqi Anwari, Mohammad; Joya Shafiq , Ahmad (Interdisciplinary Approaches to Medicine, 2024)
Bad breath, or halitosis, is a common medical condition that affects a significant portion of people worldwide. The cause of it is volatile molecules that might come from extra-oral or oral sources, both diseased and non-pathological. Halitosis can be caused by a variety of other factors, many of which are ignored, although poor dental hygiene is frequently the primary offender. These include disorders associated to the nose, throat, and bodily systems as a whole, which result in a production of odorous gasses released through the mouth. Halitosis can result from a number of illnesses, including tonsillitis, sinusitis, and some systemic conditions. In addition to these illnesses, halitosis can also be caused on by a few drugs and lifestyle behaviors including drinking alcohol and smoking. The majority of people who complain about halitosis seek therapy at a clinic because it has an adverse effect on their daily activities. However, some people with halitosis are not even aware that they have the condition. Numerous methods can be used to determine halitosis. Treatment and management of halitosis effectively require an understanding of its numerous causes. Key words: ENT, etiology, extra-oral, halitosis, pseudohalitosis, systemic